The role of chocolate web-based communication in a regional context: Its implication for open innovation - Simone Blanc; Valentina Maria Merlino; Alice Versino; Giulia Mastromonaco; Antonina Sparacino; Stefano Massaglia; Danielle Borra (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Background: This research investigates the web-based communication and promotion strategies applied by a sample of selected chocolatiers in Piedmont, a region in the northwest of Italy known for its ancient chocolate-making tradition. Methods: the AGIL scheme was used (A-adaptation, which evaluates the persuasive approach; G-goal achievement, which evaluates the informative approach; I-integration, which evaluates the communicative approach; and L-latent model, which evaluates the identity approach). Each A-G-I-L category, subdivided into subcategories containing variables, was specifically evaluated during the analysis of the companies' websites carried out by a group of experts. The five experts assigned a score for each variable and subcategory to each site. The average subcategory and category scores for each website were analyzed using principal component analysis, which allowed three communicative orientations to be defined: classic, consumer-centered, international-oriented. Results: In general, the results show a strong link between the tradition of artisan chocolate producers and the desire to create a relationship of trust in the brand on the part of consumers. Conclusions: This research is the first to contribute to the field of chocolate web-communication and provides a picture of a local production reality; it is interesting in terms of chocolate promotion styles based on the combination of tradition and innovation.
Keywords: 650; AGIL scheme; chocolate; claims; open innovation; web-based communication